FAKTOR YANG MEMPENGARUHI INTEGRITAS LAPORAN KEUANGAN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE - Safira, Intan; Susanti, Merry (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study aims to find out how leverage, institutional ownership, firm size, intellectual capital, and audit tenure affect the integrity of financial statement in property and real estate sector listedon the IDX for the period 2019-2021. This sample was selected using purposive sampling method with valid datas was 66 data. Data processing techniques using eviews version 12 which is used to process secondary data. The result of this study indicate that leverage, intellectual capital, and audit tenure do not have significant positive affect on the integrity of financial statement. Institutional ownership has a significant positive affect and company size has a non-significant positive affect on the integrity of financial statement. The implication of this study is that companies must consider of internal and external factors.